Effects of Different Packaging Methods on the Microbial Diversity in Chilled Chicken - Xutao MAI; Wenzhuo WANG; Yuhang ZHENG; Fang LIU; Zhilan SUN; Weimin XU (Shipin gongye ke-ji, 2023)
To investigate the effects of different packaging methods on microbial composition of chilled chicken during storage, the microbial diversity was analyzed by Illumina MiSeq high-throughput sequencing. The results showed that the modified atmosphere packaging (MAP), the vacuum packaging (VP) and the nitrogen-filled packaging (N2) could significantly reduce the number of microorganisms and volatile base nitrogen during refrigeration at 4 °C compared with the pallet packed (PP) group. High-throughput sequencing showed that the bacterial species richness of chilled chicken was high in the early stage of storage. The dominant bacteria of chilled chickens in PP group at the later stage of storage were Pseudomonas, Brochothrix, Acinetobacter and Shewanella. It indicated that they could tolerate lower temperatures. Compared with the PP group, the abundance of Pseudomonas and Acinetobacter in MAP group decreased by 14.8% and 9.2%, respectively, while nitrogen-filled packaging reduced the abundance of Acinetobacter and Shewanella. by 9.6% and 7.4%, respectively. The abundance of Acinetobacter and Brochothrix decreased significantly by 8% and 5.6% after vacuum packaging. Different packaging methods could have a greater impact on the flora in chilled chicken meat. All three types of packaging could inhibit the growth of Acinetobacter and MAP had a better inhibitory effect on Pseudomonas, while nitrogen-filled packaging and vacuum packaging had a better inhibitory effect on Shewanella and Brochothrix. This study also provides a theoretical basis for the future packaging methods used in chilled chicken meat.